2014
DOI: 10.1152/ajpcell.00083.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of anion exchangers in Cl and HCO3 secretion by the human airway epithelial cell line Calu-3

Abstract: Despite the importance of airway surface liquid pH in the lung's defenses against infection, the mechanism of airway HCO3- secretion remains unclear. Our aim was to assess the contribution of apical and basolateral Cl-/HCO3- exchangers to Cl- and HCO3- transport in the Calu-3 cell line, derived from human airway submucosal glands. Changes in intracellular pH (pHi) were measured following substitution of Cl- with gluconate. Apical Cl- substitution led to an alkalinization in forskolin-stimulated cells, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 63 publications
5
20
1
Order By: Relevance
“…These data suggest that VIP receptor activation or direct cAMP elevation with forskolin can activate both Cland HCO3secretion directly through CFTR. We found no evidence for Cl -/HCO3exchanger-mediated HCO3efflux in primary serous cells (Supplemental Figure 2), suggesting CFTR is the main HCO3efflux pathway during cAMP stimulation, agreeing with recent Calu-3 studies suggesting CFTR sustains HCO3secretion (88,89) instead of the pendrin Cl -/HCO3exchanger (90,91).…”
Section: Vip Stimulates Both Cland Hco3secretion From Airway Gland Sesupporting
confidence: 89%
“…These data suggest that VIP receptor activation or direct cAMP elevation with forskolin can activate both Cland HCO3secretion directly through CFTR. We found no evidence for Cl -/HCO3exchanger-mediated HCO3efflux in primary serous cells (Supplemental Figure 2), suggesting CFTR is the main HCO3efflux pathway during cAMP stimulation, agreeing with recent Calu-3 studies suggesting CFTR sustains HCO3secretion (88,89) instead of the pendrin Cl -/HCO3exchanger (90,91).…”
Section: Vip Stimulates Both Cland Hco3secretion From Airway Gland Sesupporting
confidence: 89%
“…Our laboratory [ 14 , 15 ] and others [ 24 ] have previously reported that Cl − /HCO 3 − exchange occurs across the basolateral membrane in non-stimulated Calu-3 cells. In support of these findings, intracellular pH measurements showed that removal of basolateral Cl − caused an intracellular alkalinization of 0.36 ± 0.02 units ( n = 8; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that AE2 is expressed in the airways [ 1 , 12 , 55 ] and immunostaining experiments performed on polarized Calu-3 cells have localized the expression of AE2 to the basolateral membrane [ 32 ]. Our laboratory [ 14 , 15 ] and others [ 24 ] have recently demonstrated that a functional Cl − /HCO 3 − exchanger is present at the basolateral surface of Calu-3 cells under resting conditions, with features consistent with AE2. In addition, Huang et al [ 18 ] showed that intracellular alkalinization produced by basolateral Cl − removal was decreased by 80% in SLC4A2 knockdown Calu-3 cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular chloride (Cl − ) is the major anion in living cells and plays a crucial role in maintaining cellular functions in many cell types [1][2][3][4][5][6][7][8], such as cell volume [3,6], intracellular pH [9] and fluid secretion [10,11]. MQAE, a fluorescent Cl − indicator, has been found to be a useful fluorescence dye for noninvasive measurements of the intracellular Cl − concentration ([Cl − ] i ) [12][13][14][15][16][17], with a number of advantageous properties.…”
Section: Introductionmentioning
confidence: 99%